B-RAF and N-RAS mutations are preserved during short time in vitro propagation and differentially impact prognosis - Ugurel, Selma; Gast, Andreas; Sucker, Antje; Rittgen, Werner; Hemminki, Kari; Kumar, Rajiv; Schadendorf, Dirk (PLOS ONE, 2007)
In melanoma, the RAS/RAF/MEK/ERK signalling pathway is an area of great interest, because it regulates tumor cell proliferation and survival. A varying mutation rate has been reported for B-RAF and N-RAS, which has been largely attributed to the differential source of tumor DNA analyzed, e.g., fixed tumor tissues or in vitro propagated melanoma cells. Notably, this variation also interfered with interpreting the impact of these mutations on the clinical course of the disease. Consequently, we investigated the mutational profile of B-RAF and N-RAS in biopsies and corresponding cell lines from metastatic tumor lesions of 109 melanoma patients (AJCC stage III/IV), and its respective impact on survival. 97 tissue biopsies and 105 biopsy-derived cell lines were screened for B-RAF and N-RAS mutations by PCR single strand conformation polymorphism and DNA sequencing. Mutations were correlated with patient survival data obtained within a median follow-up time of 31 months. B-RAF mutations were detected in 55% tissues and 51% cell lines, N-RAS mutations in 23% tissues and 25% cell lines, respectively. There was strong concordance between the mutational status of tissues and corresponding cell lines, showing a differing status for B-RAF in only 5% and N-RAS in only 6%, respectively. Patients with tumors carrying mutated B-RAF showed an impaired median survival (8.0 versus 11.8 months, p = 0.055, tissues; 7.1 versus 9.3 months, p = 0.068, cell lines), whereas patients with N-RAS-mutated tumors presented with a favorable prognosis (median survival 12.5 versus 7.9 months, p = 0.084, tissues; 15.4 versus 6.8 months, p = 0.0008, cell lines), each in comparison with wildtype gene status. Multivariate analysis qualified N-RAS (p = 0.006) but not B-RAF mutation status as an independent prognostic factor of overall survival. Our findings demonstrate that B-RAF and N-RAS mutations are well preserved during short term in vitro propagation and, most importantly, differentially impact the outcome of melanoma patients.
Gesehen am 05.02.2021